Prioritas Hambatan Green Management Terhadap Industri dan UMKM dalam Perspektif Lingkungan, Sosial dan Ekonomi - Junita Junita; Asmawati Asmawati; Isthafan Najmi (Jurnal Serambi Engineering, 2023)
Many companies have been consuming natural resources and energy in unsustainable systems in recent years. This has released many greenhouse gases and has caused various problems, especially for the environment, social and economic, originating from waste disposal and climate change, especially at the local level. However, many organizations have started implementing their work system with Green Management. This is due to the growing concern over pollution, depletion of natural resources and global warming. The application of Green Management to the world of work currently has various obstacles. These bottlenecks can be reduced by prioritizing bottlenecks as critical so that higher priority constraints can be used first to address issues more effectively with resources. Priorities like this are crucial, especially for developing MSMEs with minimal resources. This paper specifically aims to identify the factors hindering Green Management's implementation. The TOPSIS fuzzy method is used in making decisions by prioritizing obstacles from an environmental, social, and economic perspective. The results of the investigation indicated that lack of awareness/information, technology risks and weak policies were obstacles to implementing GM. Prioritizing barriers with different perspectives is one way to assist in making decisions or policies, especially for industry and MSMEs, in mitigating these obstacles more effectively.